Remove, recycle, degrade: regulating plasma membrane protein accumulation - Rodriguez-Furlan, Cecilia; Minina, Alyona; Hicks, Glenn R. (The plant cell, 2019)
Interactions between plant cells and the environment rely on modulation of protein receptors, transporters, channels, and lipids at the plasma membrane (PM) to facilitate intercellular communication, nutrient uptake, environmental sensing, and directional growth. These functions are fine-tuned by cellular pathways maintaining or reducing particular proteins at the PM. Proteins are endocytosed, and their fate is decided between recycling and degradation to modulate localization, abundance, and activity. Selective autophagy is another pathway regulating PM protein accumulation in response to specific conditions or developmental signals. The mechanisms regulating recycling, degradation, and autophagy have been studied extensively, yet we are just now addressing their regulation and coordination. Here, we (1) provide context concerning regulation of protein accumulation, recycling, or degradation by overviewing endomembrane trafficking; (2) discuss pathways regulating recycling and degradation in terms of cellular roles and cargoes; (3) review plant selective autophagy and its physiological significance; (4) focus on two decision-making mechanisms: regulation of recycling versus degradation of PM proteins and coordination between autophagy and vacuolar degradation; and (5) identify future challenges.
Gesehen am 09.04.2020